A large-scale, ultrahigh-resolution nanoemitter ordered array with PL brightness enhanced by PEALD-grown AlN coating. Issue 8 (11th February 2019) - Peng, Mingzeng; Zheng, Xinhe; Liu, Sanjie; Wei, Huiyun; He, Yingfeng; Li, Meiling; An, Yunlai; Song, Yimeng; Qiu, Peng
Abstract : A high-brightness III-nitride nanoemitter array was achieved with an ultrahigh resolution of 31 750 dpi for smart displays, advanced optical imaging, big-data optical information, and micro/nano opto-electro-mechanical systems. Abstract : III-nitride solid-state microdisplays have significant advantages, including high brightness and high resolution, for the development of advanced displays, high-definition projectors, head-mounted displays, large-capacity optical communication systems, and so forth. Herein, a high-brightness InGaN/GaN multiple-quantum-well (MQW) nanoemitter array with an ultrahigh resolution of 31 750 dpi was achieved by combining a top-down fabrication with surface passivation of plasma-enhanced atomic layer deposition (PEALD)-grown AlN coating. With regard to the nanometer-level top-down etching, the surface damage or defects on the newly-formed sidewall play a significant role in the photoluminescence (PL) quality. Note that these arrays can be effectively passivated by the PEALD-grown AlN coating with an over 345% PL enhancement. In addition, a sharp band bending at the interface of the luminescent InGaN QW and the AlN coating layer can electrically drift away the photogenerated electrons from the surface traps; this leads to enhancement of the bulk PL radiative recombination with a fast PL decay rate. Therefore, we have demonstrated a feasible way for realizing an advanced nanoemitter array with both high brightness and ultrahigh resolution for future smart displays, high-resolution imaging, big-data optical information systems and so on.